AN INNOVATIVE APPROACH TO THE DEVELOPMENT OF STUDENTS’ MOVEMENT SKILLS AND COMPETENCIES IN PHYSICAL EDUCATION CLASSES - Xojimurodova, Mahliyoxon; Inomov, Faxriddin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article is aimed at developing students' movement skills and abilities by effectively mastering physical exercises in physical education classes. It is intended to increase the knowledge of the students about the process of physical education.